ON THE ISSUE OF CLEANING AND SORTING OF DENT SEEDS (Collection of research papers «PROGRESSIVE TECHNIQUE AND TECHNOLOGIES OF FOOD PRODUCTION ENTERPRISES, CATERING BUSINESS AND TRADE», 2025)
The results of the study of the physical and mechanical characteristics and separation of dill seeds from weed seeds, the results of sorting dill seeds and determining the similarity of seeds of each fraction are presented, which indicates the relevance of this work. An analysis of recent studies and publications shows that dill is an annual, popular garden plant that is grown as a spice for the food industry. The purpose of the research is to substantiate the processes of cleaning dill seeds from weed seeds and sorting them by size characteristics. The article uses theoretical and computational-experimental methods using an electron microscope and the Compass-3D program. Dill seeds of the 2024 harvest, grown at the Institute of Vegetable and Melon Growing of the NAAS of Ukraine, were used for the research. It was established that a large number of weeds and mineral impurities get into dill seeds when they are harvested. The results of measuring the geometric dimensions of the width and length of dill seeds and weed plants are presented, which were carried out using image fixation with an electron microscope with subsequent transfer of images to the Compass program, in which seed size measurements were carried out. A micrometer was used to measure seed thickness. The work shows that special machines for cleaning dill seeds are not produced, but general-purpose grain cleaning machines are used, the most popular of which are sieve machines or separators with pneumatic-sieve-trier working bodies. Cleaning and sorting of dill seeds was carried out on laboratory sieves and checking for similarity of the obtained fractions, showed high efficiency of cleaning and sorting of dill seeds by size, as stated in the conclusions to the work.
Keywords: dill seeds; sizes; weed seeds; separation; sorting; germination